Dark, bright and singular optical solutions of the Kaup-Newell model with two analytical integration schemes - Esen, Handenur; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa (ELSEVIER GMBH, 2022)
We have searched for optical solutions of Kaup-Newell equation (KNE) used in nonlinear optical and plasma physics, which have a very important role in the class of derivative nonlinear Schrodinger equations (dNLSEs). To obtain exact wave solutions of the proposed model, two analytical techniques, recently presented as new Kudryashov's method and the generalized projective Riccati equations method (GPREM) have been applied for the first time. These two methods are based on traveling wave transformation and homogeneous balance principles . The presented nonlinear partial differential equation (NLPDE) has been converted to ordinary differential equation (ODE) using traveling wave transformation. Thus, new analytical solutions have been obtained by applying the proposed methods. The new solitons and other traveling wave solutions acquired will be a motivation to researchers working in engineering and applied physics. Various constraints have been used to ensure the validity of the obtained solutions and to get the most appropriate solutions. To illustrate the physical phenomena of this model, 2D, 3D and contour plots of some derived solutions have been depicted with explanatory graphics.
Keywords: Kaup-Newell equation; New Kudryashov?s method; Generalized projective Riccati equations method; DARBOUX TRANSFORMATION; BIREFRINGENT FIBERS; LAW NONLINEARITY; EQUATION; SOLITONS; EXPANSION; Optics